Innovation of New System of Water Supply for Wudhu - F Mat Taib, C.; S Iqubal, S.; Md Yusof, Fauziah; Kasolang, S. (International Journal of Engineering and Technology, 2018)
Wudhu (ablution) ritual is an activity of cleaning physical parts for Muslims to perform their prayer five times per day. During this wudhu ritual process, the water is allowed to run free and drain away. At-times, this has caused some concerns particualrly on water wastage. Many organizations in Malaysia such as AACE Technologies Sdn. Bhd. came out with a solution and steps as â€œAuto Wudu Washerâ€ in order to overcome this wastage, but the result was not satisfying enough. This study introduces a wudhu system that can reduce the amount of water usage during wudhu ritual consistently by limiting around 1 litre per consumer. Generally, there were seven (7) parts that have been used in this project such as 1 litre of container, magnet, float, valve push button, washer and cap. These designs did not utilize any electronic devices. Using these parts, 2 experiments were conducted namely the current wudhu system and the upgraded wudhu system by 10 (Muslims) respectively. The result of this project confirmed that using the Upgraded Wudhu System with amount of water limited to 1 litre per consumer was better than the current wudhu system by ten times.Â Â